The Complete Chloroplast Genome Sequences of Eight Fagopyrum Species: Insights Into Genome Evolution and Phylogenetic Relationships - Fan, Yu; Jin, Ya’nan; Ding, Mengqi; Tang, Yu; Cheng, Jianping; Zhang, Kaixuan; Zhou, Meiliang (Frontiers in Plant Science, 2021)
Buckwheat (Fagopyrum genus, Polygonaceae), is an annual or perennial, herbaceous or semi-shrub dicotyledonous plant. There are mainly three cultivated buckwheat species, common buckwheat (Fagopyrum esculentum) is widely cultivated in Asia, Europe, and America, while Tartary buckwheat (F. tataricum) and F. cymosum (also known as F. dibotrys) are mainly cultivated in China. The genus Fagopyrum is taxonomically confusing due to the complex phenotypes of different Fagopyrum species. In this study, the chloroplast (cp) genomes of three Fagopyrum species, F. longistylum, F. leptopodum, F. urophyllum, were sequenced, and five published cp genomes of Fagopyrum were retrieved for comparative analyses. We determined the sequence differentiation, repeated sequences of the cp genomes, and the phylogeny of Fagopyrum species. The eight cp genomes ranged, gene number, gene order, and GC content were presented. Most of variations of Fagopyrum species cp genomes existed in the LSC and SSC regions. Among eight Fagopyrum chloroplast genomes, six variable regions (ndhF-rpl32, trnS-trnG, trnC, trnE-trnT, psbD, and trnV) were detected as promising DNA barcodes. In addition, a total of 66 different SSR (simple sequence repeats) types were found in the eight Fagopyrum species, ranging from 8 to 16 bp. Interestingly, many SSRs showed significant differences especially in some photosystem genes, which provided valuable information for understanding the differences in light adaptation among different Fagopyrum species. Genus Fagopyrum has shown a typical branch that is distinguished from the Rumex, Rheum, and Reynoutria, which supports the unique taxonomic status in Fagopyrum among the Polygonaceae. In addition, phylogenetic analysis based on the cp genomes strongly supported the division of eight Fagopyrum species into two independent evolutionary directions, suggesting that the separation of cymosum group and urophyllum group may be earlier than the flower type differentiation in Fagopyrum plants. The results of the chloroplast-based phylogenetic tree were further supported by the matK and Internal Transcribed Spacer (ITS) sequences of 17 Fagopyrum species, which may help to further anchor the taxonomic status of other members in the urophyllum group in Fagopyrum. This study provides valuable information and high-quality cp genomes for identifying species and evolutionary analysis for future Fagopyrum research.